OP0291 Romosozumab Administration is Associated with Significant Improvements in Lumbar Spine and Hip Volumetric Bone Mineral Density and Content Compared with Teriparatide. (10th June 2014) - Genant, H.; Bolognese, M.; Mautalen, C.; Brown, J.; Recknor, C.; Goemaere, S.; Engelke, K.; Yang, Y.-C.; Austin, M.; Grauer, A.; Libanati, C.
Abstract : Background: Sclerostin is an osteocyte-derived inhibitor of osteoblast activity. Romosozumab, a monoclonal antibody to sclerostin, stimulates bone formation and decreases bone resorption. In a phase 2 study, romosozumab administered for 12 months increased areal bone mineral density (BMD) at the lumbar spine (LS) and total hip (TH) as measured by dual X-ray absorptiometry compared with placebo (Pbo), alendronate, and teriparatide (TPTD) in postmenopausal women with low bone mass. Objectives: To describe the effect of romosozumab on LS and TH volumetric BMD (vBMD) and bone mineral content (BMC) as measured by quantitative computed tomography (QCT) in this trial. Methods: This international, randomized, Pbo-controlled, phase 2 study enrolled postmenopausal women 55–85 years old with LS, TH, or femoral neck T-score ≤−2.0 and ≥−3.5 at all sites. QCT measurements were performed at the "total" LS (mean of L1 and L2 entire vertebral bodies) and TH in subjects receiving Pbo, subcutaneous TPTD (20 μg QD), and subcutaneous romosozumab (210 mg QM). Percentage change from baseline in integral and cortical vBMD and BMC, and trabecular vBMD was evaluated at 12 months. The analyses included subjects with baseline and ≥1 post-baseline QCT measurements. Results: Treatment with romosozumab resulted in significant increases in integral vBMD and BMC at the "total" LS and TH from baseline, and compared with Pbo and TPTD (Figure), whereas TPTD increased integral vBMD and BMC compared with Pbo at the LS but not the TH. Further differences between romosozumab and TPTD were observed in trabecular and cortical bone compartments depending on the skeletal location. At the LS, similar and significant gains from baseline ( P <0.05) in trabecular vBMD were measured with both romosozumab (+18.3%) and TPTD (+20.1%). At the TH, trabecular vBMD gains were significantly larger with romosozumab than TPTD (10.8% vs 4.2%, P =0.01). Cortical vBMD gains were larger with romosozumab compared with TPTD at the LS (13.7% vs 5.7%, P <0.0001) and TH (1.1% vs –0.9%, P =0.12). Cortical BMC gains were also larger with romosozumab compared with TPTD at both the LS (23.3% vs 10.9%, P <0.0001) and TH (3.4% vs 0.0%, P =0.03). Conclusions: Romosozumab significantly increased vBMD and BMC at the "total" LS and TH compared with Pbo and TPTD in postmenopausal women with low bone mass. The gains, observed in both the trabecular and cortical compartments, support the continued clinical investigation of romosozumab as a potential treatment for postmenopausal women with osteoporosis with established BMD deficits and at increased fracture risk. Disclosure of Interest: H. Genant Grant/research support: Amgen, GSK, Roche, Novartis, Lilly, Servier, Pfizer, Consultant for: Amgen, GSK, Roche, Novartis, Lilly, Servier, Pfizer, M. Bolognese Grant/research support: Amgen; Lilly, Regeneron, Speakers bureau: Amgen, C. Mautalen Consultant for: Servier, Merck, J. Brown Grant/research support: Amgen, Eli Lilly, Merck, Novartis, Warner Chilcott, Consultant for: Amgen, Eli Lilly, Speakers bureau: Amgen, Eli Lilly, C. Recknor: None declared, S. Goemaere Grant/research support: Amgen, Novartis, MSD, Consultant for: UCB, Eli Lilly, Rottapharma, Speakers bureau: Amgen, MSD, Servier, Eli Lilly, Novartis, Takeda, Willpharma, K. Engelke Grant/research support: German Ministry for Research and Technology, Consultant for: Amgen, Employee of: Synarc Inc, Y.-C. Yang Shareholder of: Amgen, Employee of: Amgen, M. Austin Shareholder of: Amgen, Employee of: Amgen, A. Grauer Shareholder of: Amgen, Employee of: Amgen, C. Libanati Shareholder of: Amgen, Employee of: Amgen DOI: 10.1136/annrheumdis-2014-eular.2526